Gender and social inclusion in community water resource management: lessons from two districts in the Himalayan foothills and the Terai in Nepal - Raut, Manita; Varady, R. G.; Rajouria, Alok (Informa UK Limited, 2023)
Despite decades of concerted efforts to address the problem, Nepal’s rural water supply sector continues to be laced with gender and social exclusion. This study provides insights from community water-user groups in two geographically and socially diverse contexts to better understand, from a gender and social inclusion perspective, and through institutional bricolage, how some water-user groups adapt to local contexts, shaping varied group dynamics that are not always equitable. Findings reveal that policies promoting social inclusion are difficult to implement amid the complex web of social and economic factors associated with community-managed water supply systems.